Air-Pollution-Mediated Microbial Dysbiosis in Health and Disease: Lung–Gut Axis and Beyond - Md Habibul Hasan Mazumder; Salik Hussain (Journal of Xenobiotics, 2024)
Growing evidence suggests physiological and pathological functions of lung and gut microbiomes in various pathologies. Epidemiological and experimental data associate air pollution exposure with host microbial dysbiosis in the lungs and gut. Air pollution through increased reactive oxygen species generation, the disruption of epithelial barrier integrity, and systemic inflammation modulates microbial imbalance. Microbiome balance is crucial in regulating inflammation and metabolic pathways to maintain health. Microbiome dysbiosis is proposed as a potential mechanism for the air-pollution-induced modulation of pulmonary and systemic disorders. Microbiome-based therapeutic approaches are increasingly gaining attention and could have added value in promoting lung health. This review summarizes and discusses air-pollution-mediated microbiome alterations in the lungs and gut in humans and mice and elaborates on their role in health and disease. We discuss and summarize the current literature, highlight important mechanisms that lead to microbial dysbiosis, and elaborate on pathways that potentially link lung and lung microbiomes in the context of environmental exposures. Finally, we discuss the lung–liver–gut axis and its potential pathophysiological implications in air-pollution-mediated pathologies through microbial dysbiosis.